PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN PROFESIONALISME TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KOTA PASURUAN - Oni Farah; Sri Hastari; Hari Wahyuni (Bajang Institute, 2023)
The Pasuruan City Regional Personnel Agency is enggaged in public services which must improve employee perfomance by improving the quality of human resources and employee professionalism in order to achieve organizational goals. This study aims to determine the effect of the quality of human resources and professionalism on the perfomance of employees at the Pasuruan City Regional Civil Service Agency. The population studied was all employees of the Pasuruan City Regional Personnel Agency. Sampling of this research used saturated sampling technique, namely all populations were sampled, namely 38 respondent. The type of research data is primary data using multiple linier regression analysis. The results of the study show that the quality of human resources and professionalism had a significant effect on the perfomance.There was an increase in employee perfomance compared to the previous year indicated by organizational assesment. The quality of human resources has a significant effect on the perfomance of employees. This is shown by Employees have good physical abilities, expertise, have a higher education and utilizing technology. Professionalism has a significant effect on the perfomance of employee. This is shown by employees providing maximun service, having high professionalism and always being responsible for their work